Miscarriage, Perceived Ostracism, and Trauma: A Preliminary Investigation - Wesselmann, Eric D.; Parris, Leandra (Frontiers in Psychology, 2022)
Miscarriage is a traumatic experience with serious mental health implications. Friends and family members are often uncomfortable with and avoid discussing the topic with bereaved individuals, potentially making them feel ostracized (i.e., being ignored and excluded), contributing to their mental health concerns. We investigated the correlation between posttraumatic stress symptoms, perceived ostracism, and recalled grief intensity measures in a sample of cisgender women (N = 97) who have had a miscarriage. These participants were recruited using Qualtrics’s Panel Recruitment Services. Women’s perceived ostracism correlated positively with posttraumatic stress symptoms and negatively with grief congruence (i.e., the degree to which they felt that their miscarriage process was as satisfactory as possible, given they had to experience it). Perceived ostracism also explaining additional variance in posttraumatic stress symptoms when considered alongside grief intensity measures (e.g., congruence).